Bioinvasions and globalization : ecology, economics, management, and policy - Perrings, Charles; Mooney, Harold A.; Williamson, M. H. (Mark Herbert) (Oxford : Oxford University Press, 2010)
This volume addresses the issue of biological invasions from both an ecological and economic perspective, providing an in-depth evaluation of the science and its implications for managing the causes and consequences of one of the most pressing environmental issues facing humans today.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Biological invasions; Globalization -- Environmental aspects; Introduced organisms -- Control -- Government policy